A Literature Review of The Influence of Competence and Incentives on Nurses' Performance through Motivation - Dedhy Sastiyono; Anton Agus Setyawan; Safari Wahyu Jatmiko (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
Purpose: Hospital management prioritizes improving nursing staff performance to enhance patient satisfaction. This study aims to examine the effect of competence and incentives with motivation as a mediator variable on nurse performance.Methodology: a Systematic Literature Review (SLR) approach. Results: A total of 27 articles were selected from 1,204 articles searched between 2021 and 2025. The results showed that the majority of studies found that competence, incentives, and motivation had a positive and significant effect on nurses' performance, both partially and simultaneously. However, one study showed that professional competence did not have a significant effect on nursing performance, because nurses continued to carry out their duties in accordance with established standard operating procedures. Applications/Originality/Value: This study differs from previous studies because it analyzes the influence of four variables, namely the number of articles studied, accessibility in full text and pdf form.